Language shaming practices on Youtube : ideologies of English in Vietnam - Nguyen, Hoa Dieu (2019)
As English has gradually become the global language, users of this lingua franca find themselves constantly challenged and intimidated by a new wave of linguistic attack online known as “language shaming practices on YouTube.” Language shaming in general or English shaming in particular can be understood as any forms of interaction that degrade any certain ways of using language.